Viajantes, mareantes e fronteiriços : relações interculturais no movimento das Monções - Século XVIII - Carvalho, Francismar Alex Lopes de (2006)
This study analyzes the intercultural relationships among the populations involved in the movement of the monsoons. Monsoons were the convoys of canoes that conducted the travelers, for difficult fluvial route, of São Paulo to Cuiabá starting from the decade of 1720 to middles of the 19th century. In those trips, the histories of some social groups were interlaced with differentiated cultural lines: travelers, sailors and frontiers. Starting from a relational approach, the moments of contact among those populations are analyzed here emphasizing the conflicts and alliances, hybridizations, re-creation or maintenance of the cultural lines. The analytical focus is addressed for the moments of encounter and establishment of social relationships these following groups: (a) the travelers that proceeded in the monsoonal journey, (b) the mameluco workers of the canoes and (c) the frontier ethnic groups rulers of the territories through where passed the routes. The main intention is, therefore, to try to understand the way as each social group involved in the movement of the monsoons guided their practices and strategies due to the contact situation propitiated by those trips. The First Part of the present study is an analysis of the following roads to the borders of the Portuguese colony in America of the 18th century, looking at the decisive contradiction between the routes wanted by the adventitious and the territorialities of the local ethnic groups. Really, he trips to the distant West became possible because some sections of the population from São Paulo specialized deeply in the practices of backwoods, due to the cultural exchange with the natives. Those cultural flows were incorporating in the workers' of the monsoonal canoes. That subject is analyzed in the Second Part of this study. Finally, the Third Part analyzes the complex political system of ethnic alliances among the populations of the distant West, and the actions promoted by Mbayá-Guaykuru, Payaguá, and other indigenous groups to defend their territories. At the same time, this part analyzes the system of alliances of the adventitious, Portuguese and Spanish, elaborated to allow the wanted regular access to the territories.